Philosophy of Language in the Age of Artificial Intelligence: A Philosophical–Analytical Study of the Limits of Understanding and the Possibilities of Meaning Production (Comprehensive Journal of Science, 2026)
This study addresses the problematics of the philosophy of language in the era of artificial intelligence through a critical analytical examination of the limits of understanding and the possibilities of meaning production. It begins by tracing the transformations in the philosophy of language, from structuralism and logical approaches to pragmatic and interpretive frameworks, and juxtaposes these classical and contemporary conceptions with the capabilities of artificial intelligence systems in natural language processing and text generation. The study aims to highlight the fundamental distinction between human language, conceived as a historically and contextually embedded intentional experience, and artificial language, conceived as a computational system operating on formal and probabilistic processes. It emphasizes that, despite the precision and coherence of machine-generated output, it remains a linguistic simulation that does not attain the philosophical understanding of meaning. Furthermore, the research seeks to conceptualize the notions of meaning and understanding in the philosophy of language in light of contemporary technological transformations, and to open new philosophical horizons that balance the assimilation of AI achievements with the preservation of human-centered meaning and its interpretive value.
Keywords: Philosophy of Language – Artificial Intelligence – Linguistic Semantics – Understanding – Meaning – Meaning Production – Hermeneutics – Structuralism Approaches – Pragmatics